The Influence of Perceived Benefits, Perceived Ease of Use, and Service Features on Customer Satisfaction with the Use of the PLN Mobile Application at PT PLN (PERSERO) UP3 Palembang - Rosyada, Amrina; Alie, Juhaini (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2025)
The research objective is specifically to determine the influence of the variables Influence of Perceived Benefits, Perceived Convenience, and Service Features on Customer Satisfaction (Case Study on Using the PLN UP3 Palembang Mobile PLN Application).